2002
DOI: 10.1081/iph-120014730
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOSTIMULATING EFFECTS OF ACIDIC POLYSACCHARIDES EXTRACT OFPANAX GINSENGON MACROPHAGE FUNCTION

Abstract: The root of Panax ginseng C. A. Meyer is one of the most popular natural tonics in oriental countries. In this study, we have isolated polysaccharide fraction of Panax ginseng (ginsan) and examined its effect on the function of murine peritoneal macrophages. When macrophages were treated with ginsan, cytotoxic activity against B16 melanoma cells was significantly induced. In addition, the levels of cytokines, including tumor necrosis factor-alpha (TNF-alpha), interleukin-1beta (IL-1beta), IL-6 and Interferon-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(80 citation statements)
references
References 23 publications
4
72
1
3
Order By: Relevance
“…15 Furthermore, it was reported that ginseng has immunostimulating activity. 16,17 Immune responses are known to play essential roles in host defense mechanisms, but may also cause general toxic, idiosyncratic, and allergic adverse reactions (which are sometimes associated with immunostimulating agents), thereby resulting in exacerbation rather than suppression of some disease processes. 18 It is possible that RG could occasionally cause skin safety problems, such as allergenic responses.…”
Section: Introduction Gmentioning
confidence: 99%
“…15 Furthermore, it was reported that ginseng has immunostimulating activity. 16,17 Immune responses are known to play essential roles in host defense mechanisms, but may also cause general toxic, idiosyncratic, and allergic adverse reactions (which are sometimes associated with immunostimulating agents), thereby resulting in exacerbation rather than suppression of some disease processes. 18 It is possible that RG could occasionally cause skin safety problems, such as allergenic responses.…”
Section: Introduction Gmentioning
confidence: 99%
“…45 In another study, acid polysaccharides of ginseng were previously found to activate macrophage cells that produce proinflammatory cytokines, including IFNs, tumor necrosis factor-a, IL-1b, and IL-6. 21 In addition, a mechanistic study demonstrated that spleen cells and peritoneal macrophage cells that were stimulated by ginseng extract produced tumor necrosis factor-a and IFN-c inflammatory cytokines in a Toll-like receptor-4-dependent manner. 23 In contrast, ginseng was shown to attenuate lipopolysaccharide-induced pro-inflammatory mediators, including tumor necrosis factor-a and IL-6 in a macrophage cell line.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13][14][15][16] In clinical studies, ginseng has been shown to have beneficial effects on improving the survival and the quality of life among breast cancer patients, 17 in a placebocontrolled pilot trial of cancer patients, 18 in patients infected with human immunodeficiency virus, 19,20 and on reducing the occurrence of gastric cancer. 21 Immunomodulatory effects are among the beneficial properties attributed to ginseng extract. The nature of these activities and their underlying mechanisms remain largely unknown and were reported to be diverse depending on types of diseases and/or biological assessment methods: some studies demonstrated anti-inflammatory activities, while others reported proinflammatory effects.…”
Section: Introduction Imentioning
confidence: 99%
“…Clinical trials have provided some evidence that they can improve survival 105 . The polysaccharide complexes and extracts include constituents of Coriolus versicolor (whose extract is called Krestin, PSK, or PSP) 106-118 , Ganoderma lucidum [119][120][121] , Grifola frondosa (maitake MD-fraction) 122-127 , Astragalus membranaceus 128 , Panax ginseng [129][130][131][132] , and various other medicinal mushrooms [133][134][135] .…”
Section: Herbsmentioning
confidence: 99%